A comparison of chemical composition, bioactive components and antioxidant activity of natural and cultured Cordyceps sinensis. Issue 1 (September 2015) - Wang, Junqiao; Kan, Lijiao; Nie, Shaoping; Chen, Haihong; Cui, Steve W.; Phillips, Aled O.; Phillips, Glyn O.; Li, Yajing; Xie, Mingyong
Abstract This study investigates the chemical composition and bioactive components of three natural Cordyceps sinensis and one culture mycelium, and further compares the antioxidant properties of their aqueous extracts. The contents of crude fat and total amino acids were significantly higher in cultured sample. Glutamic acid was the most abundant amino acid in all samples; arginine was the second major amino acid in natural samples, while in cultured sample it contained large quantity of aspartic acid and leucine. The contents of minerals, except for Cr, Mo, Sn, V and Cd, were significantly different between natural and cultured samples. The content of mannitol in natural samples was significantly higher, ranging from 9.85% to 11.51%, while in the mycelium the value was less than half. On the contrary, the levels of polysaccharide, adenine and adenosine in cultured sample amounted to 10.43%, 0.50 mg/g and 2.61 mg/g, respectively, considerably higher than the natural ones. There was no difference in content of guanosine among four samples. Cordycepin was not detected in the four samples examined. Additionally, in vitro antioxidant activity evaluations showed that water extracts of cultured sample had a stronger ability in scavenging DPPH and hydroxyl radicals, as well as a higher reducing power.